Discovery of a First-in-Class Gut-Restricted RET Kinase Inhibitor as a Clinical Candidate for the Treatment of IBS - Schenck Eidam, Hilary; Russell, John; Raha, Kaushik; DeMartino, Michael; Qin, Donghui; Guan, Huiping Amy; Zhang, Zhiliu; Zhen, Gong; Yu, Haiyu; Wu, Chengde; Pan, Yan; Joberty, Gerard; et al. (ACS medicinal chemistry letters, 2018)
Abdominal pain and abnormal bowel habits represent major symptoms for irritable bowel syndrome (IBS) patients that are not adequately managed. Although the etiology of IBS is not completely understood, many of the functions of the gastrointestinal (GI) tract are regulated by the enteric nervous system (ENS). Inflammation or stress-induced expression of growth factors or cytokines may lead to hyperinnervation of visceral afferent neurons in GI tract and contribute to the pathophysiology of IBS. Rearranged during transfection (RET) is a neuronal growth factor receptor tyrosine kinase critical for the development of the ENS as exemplified by Hirschsprung patients who carry RET loss-of-function mutations and lack normal colonic innervation leading to colonic obstruction. Similarly, RET signaling in the adult ENS maintains neuronal function by contributing to synaptic formation, signal transmission, and neuronal plasticity. Inhibition of RET in the ENS represents a novel therapeutic strategy for the normalization of neuronal function and the symptoms of IBS patients. Herein, we describe our screening effort and subsequent structure–activity relationships (SARs) in optimizing potency, selectivity, and mutagenicity of the series, which led to the discovery of a first-in-class, gut-restricted RET kinase inhibitor, 2-(4-(4-ethoxy-6-oxo-1,6-dihydropyridin-3-yl)-2-fluorophenyl)-N-(5-(1,1,1-trifluoro-2-methylpropan-2-yl)isoxazol-3-yl)acetamide (15, GSK3179106), as a clinical candidate for the treatment of IBS. GSK3179106 is a potent, selective, and gut-restricted pyridone hinge binder small molecule RET kinase inhibitor with a RET IC50 of 0.3 nM and is efficacious in vivo.